2005
DOI: 10.1037/0022-006x.73.5.893
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to treatment in a randomized clinical trial of marital therapy.

Abstract: This study investigated demographic, intrapersonal, and interpersonal predictors of treatment response in a randomized clinical trial of 134 distressed married couples, which examined traditional (N. S. Jacobson & G. Margolin, 1979) and integrative (N. S. Jacobson & A. Christensen, 1996) behavioral couple therapy. Results based on hierarchical linear modeling revealed that interpersonal variables were the strongest predictors, but their effects were largely limited to predicting initial marital dissatisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 36 publications
4
71
4
Order By: Relevance
“…In earlier research (Conradi et al, 2006), we found a correlation of 0.61 (p < .01). In contrast with neuroticism as examined by Atkins et al (2005) and B. R. Baucom et al (2009), we found model of self to be a significant predictor for treatment outcome. However, the sample on which Atkins et al's (2005) and B. R. Baucom et al's (2009) studies were based, was relatively functional, with only 16% having a current psychiatric diagnosis, whereas in our sample 76.5% had an ICD-10 diagnosis.…”
Section: Working Model Of Self and Psychopathologycontrasting
confidence: 52%
See 4 more Smart Citations
“…In earlier research (Conradi et al, 2006), we found a correlation of 0.61 (p < .01). In contrast with neuroticism as examined by Atkins et al (2005) and B. R. Baucom et al (2009), we found model of self to be a significant predictor for treatment outcome. However, the sample on which Atkins et al's (2005) and B. R. Baucom et al's (2009) studies were based, was relatively functional, with only 16% having a current psychiatric diagnosis, whereas in our sample 76.5% had an ICD-10 diagnosis.…”
Section: Working Model Of Self and Psychopathologycontrasting
confidence: 52%
“…In contrast with neuroticism as examined by Atkins et al (2005) and B. R. Baucom et al (2009), we found model of self to be a significant predictor for treatment outcome. However, the sample on which Atkins et al's (2005) and B. R. Baucom et al's (2009) studies were based, was relatively functional, with only 16% having a current psychiatric diagnosis, whereas in our sample 76.5% had an ICD-10 diagnosis. Moreover, Atkins et al (2005) and B. R. Baucom et al (2009) applied marital satisfaction as an outcome measure, whereas in our study psychopathology (next to problem-solving capacity) served as a criterion measure.…”
Section: Working Model Of Self and Psychopathologycontrasting
confidence: 52%
See 3 more Smart Citations